Varieties of English. - Mesthrie, Rajend (Mouton textbook., 2008)
This volume gives a detailed overview of the varieties of English spoken in Africa, South and Southeast Asia, including L1 varieties (such as White South African or St Helena English), L2 varieties (such as Cameroon, Pakistani, or Malaysian English) as well as pidgins and creoles (such as Nigerian or Ghanaian Pidgin). The chapters, written by widely acclaimed specialists, provide concise and comprehensive information on the phonological, morphological and syntactic characteristics of each variety discussed. The articles are followed by exercises and study questions. The exercises are geared towards students and can be used for classroom assignments as well as for self study in preparation for exams. Instructors can use the exercises, sound samples and interactive maps to enhance their classroom presentations and to highlight important language features. The accompanying CD-ROM contains interactive maps and speech samples that supplement the printed articles and offer material and data for further research. The rich detail found in the chapters as well as the valuable tools on the CD-Rom make this survey of English Varieties a mainstay for researchers and teachers. The content of the CD-ROM is online: http://www.varieties.mouton-content.com.